2022
DOI: 10.1371/journal.pone.0265130
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the antibody response to SARS-COV-2 vaccination amongst kidney transplant recipients at a single nephrology centre

Abstract: Background and objectives Kidney transplant recipients are highly vulnerable to the serious complications of severe acute respiratory syndrome coronavirus 2 (SARS-COV-2) infections and thus stand to benefit from vaccination. Therefore, it is necessary to establish the effectiveness of available vaccines as this group of patients was not represented in the randomized trials. Design, setting, participants, & measurements A total of 707 consecutive adult kidney transplant recipients in a single center in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 44 publications
1
34
0
Order By: Relevance
“…Then, after the general implementation of vaccinations, anti-SARS-CoV-2 assays started to be used to assess individual humoral responses to inoculation [ 5 ]. This is particularly important in certain groups of patients, such as the elderly or immunosuppressed [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Then, after the general implementation of vaccinations, anti-SARS-CoV-2 assays started to be used to assess individual humoral responses to inoculation [ 5 ]. This is particularly important in certain groups of patients, such as the elderly or immunosuppressed [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…There were 22 breakthrough infections and 3 deaths after vaccination, including 77% (17/22) infections and 13.6% (3/22) deaths in the seronegative group and only 23% (5/22) infections and 0% (0/22) deaths in the seropositive group. 38 However, this study did not use the WHO IS to get a cutoff for the responder. Therefore, there may be some non-responders (fold-index <4) in the seropositive group according to our study.…”
Section: Discussionmentioning
confidence: 97%
“…There were 22 breakthrough infections and 3 deaths after vaccination, including 77% (17/22) infections and 13.6% (3/22) deaths in the seronegative group and only 23% (5/22) infections and 0% (0/22) deaths in the seropositive group. 18 Chavarot et al reported that administration of a third dose of BNT162b2 vaccine did not improve immunogenicity in KTRs treated with belatacept without prior COVID-19. Seropositivity was only 37.1% (13/35) of KTRs after the third vaccine dose.…”
Section: Discussionmentioning
confidence: 99%
“…Chukwu et al reported clinical findings in a group of kidney transplant recipients received two doses of the SARS-CoV-2 vaccine. 18 There were 22 breakthrough infections and 3 deaths after vaccination, including 77% (17/22) infections and 13.6% (3/22) deaths in the non-responder group and only 23% (5/22) infections and 0% (0/22) deaths in the responder group. 18 Therefore, there is an urgent need to identify SARS-CoV-2 vaccine non-responders in the vulnerable population to reduce severe COVID-19 and mortality.…”
mentioning
confidence: 90%